Chemical profile of the polar extract of Paepalanthus microphyllus (Guill.) Kunth (Eriocaulaceae) (Revista Brasileira de Ciências Farmacêuticas, 2004)
From the ethanolic extract of the capitulae of Paepalanthus microphyllus, one caffeic acid derivative (1) was isolated. The structure of the compound was characterized by spectroscopic methods, mainly 1D and 2D NMR experiments, as well as ESMS spectrometry. In addition, three flavonoids of taxonomic relevance were isolated and identified by comparison to literature data.